(untitled) (Географический вестник=Geographical bulletin, 2017)
Статья представляет собой описание пермской велосипедной экспедиции на Кунь-Лунь и Тибет в 2009 г., посвященной 170-летию со дня рождения Н.М. Пржевальского. Во время путешествия впервые были осуществлены восхождения на две вершины высотой 6200 м и 6100 м. Маршрут проходил через полюс недоступности Кунь-Луня и соединял два мощнейших узла оледенения Центрального Кунь-Луня: район г. Улуг-Музтаг и г. Шапка Мономаха. ON THE PRZHEVALSKIY’S WAY Devoted to the 170th anniversary from the date of N.M. Przhevalsky birthPermbicycle expedition on Kun-Lun andTibetin 2009 is described in the article. The expedition route touched the places where some stages of all four Central Asian expeditions of the great Russian traveller took place in the 19th century. Two summits were ascended for the first time during the travel. The 6200m summit was named Przhevalsky peak, another – 6100m - was named Roborovsky peak. Expedition route passed through Kun-Lun inaccessibility pole with more than500 kmdistance from the nearest settlements and connected two mighty freezing knots of the Central Kun-Lun: the regions of Ulug-Muztag and of Monomakh Cap mountains.